2004
DOI: 10.4141/p02-183
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Canadian weeds. 130. Amaranthus retroflexus L., A. powellii S. Watson and A. hybridus L.

Abstract: The three species are noxious weeds introduced to Canada from southern North America. Their geographical distribution has remained almost unchanged since the original paper published in 1980. The plants exhibit a high phenotypic plasticity and genetic variability and they easily adapt to a multitude of agrestal and ruderal habitats. The seeds contribute to a persistent seed bank; they exhibit a variable dormancy and polymorph germination as a result of maternal, genetic and environmental factors. Growth is rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 292 publications
1
108
1
4
Order By: Relevance
“…Along these often private farm roads lower disturbance, light intensity and use of de-icing salt potentially lead to lower ragweed abundance (Basset and Crompton 1975;DiTommaso 2004). Weeds that are more associated with fields than roadsides, but can be found along roadsides, specifically Amaranthus species (Costea et al 2004), were not observed along rural roadsides, even in the area closest to the field entrances. Although we could not do statistical analyses, this suggests that ragweed abundance along rural roadsides was not related to the general abundance of field weeds.…”
Section: Discussion Fields Field Borders and Roadsidesmentioning
confidence: 97%
“…Along these often private farm roads lower disturbance, light intensity and use of de-icing salt potentially lead to lower ragweed abundance (Basset and Crompton 1975;DiTommaso 2004). Weeds that are more associated with fields than roadsides, but can be found along roadsides, specifically Amaranthus species (Costea et al 2004), were not observed along rural roadsides, even in the area closest to the field entrances. Although we could not do statistical analyses, this suggests that ragweed abundance along rural roadsides was not related to the general abundance of field weeds.…”
Section: Discussion Fields Field Borders and Roadsidesmentioning
confidence: 97%
“…Like other Amaranthus species, Palmer amaranth seed are predominantly gravitydispersed but can also be spread by irrigation and other water flow, with the movement of birds and mammals, and through agricultural management practices such as plowing, mowing, harvesting, and spreading compost, manure or gin trash (Costea et al 2004(Costea et al , 2005Norsworthy et al 2009). Although the seeds lack specialized dispersal mechanisms, including for wind dispersal, strong winds may move them over considerable distances; a hurricane was believed to be responsible for introducing Palmer amaranth seed into a previously noninfested agricultural habitat (Menges 1987a).…”
Section: à3mentioning
confidence: 99%
“…The total number of bands that frequented with consider to molecular weights were 58 over 34 frequent polymorphic bands means that above 85 % of the bands were polymorphic (Table 2). It is worth mentioning that many unique bands appeared in the gel and for all the species studied, thus the total number of unique bands is 15(25.86%), while the total number of monomorphic bands is 9 (15.51%), which is less than the polymorphic bands percentage and that reveal the high genetic polymorphism of this Family [20]. The studied species of the Amaranthaceae family showed high polymorphism due to the genetic differences among the four studied genera and from different tolerances as drought and salinity and Weather fluctuations in Iraq.…”
Section: Resultsmentioning
confidence: 99%